The impact of evidence based journal club on decision making capacity: a pilot study - J D Lakhani; A Muley; J Lodhari (Journal of Integrated Health Sciences)
Introduction: Journal clubs (JC) are an integral part of medical curriculum. Evidence based journal clubs (EBJC) are now being preferred by some over traditional JCs claiming that EBJC answers questions regarding validity, reliability and applicability specifically. However, there is lack of studies addressing effect of EBJC on participants' understanding of results and critical appraisal capability. Methodology: This was a pilot study. To test effect of EBJC on understanding of the specific topic and improvement in decision making ability, pre and post tests were conducted before and after each assessed EBJC presentation. Results: Total 36 residents were included. 53% could not make up their mind about the acceptability of the results in the pretest. However, almost all could make a specific decision regarding reliability of results and applicability of the authors' conclusion at the end of the assessed EBJC presentation. Conclusion: We concluded that exposure to EBJC resulted in significant improvement in the participants' understanding of the article and specific decision making capacity.